Study on risk factors and angiographic pattern of coronary artery involvement in patients presenting with angina - Ramya, Neelakandan; Prabakaran, V.; Abbas, Ahmed; Shankar, Sethu Prabhu (International Journal of Advances in Medicine, 2019)
Background: Coronary artery disease has become a global health problem affecting a significant portion of population in developed as well as the developing countries. The objective of the present endeavor is to study the pattern of coronary artery involvement by coronary angiography in patients with angina and to correlate the risk factors with the pattern of coronary artery involvement. Methods: This study was done as a cross sectional study on 50 patients with angina, attending the department of Medicine and Cardiology in Aarupadai veedu medical college hospital, Pondicherry from January 2018 to March 2018, who later underwent coronary angiogram. All patients of both sexes aged above 18 years presenting with history of angina both stable and unstable were included in the study, while those with previous history of congestive cardiac failure, malignant diseases, chronic kidney disease, autoimmune disorders were excluded from the study. Study was carried out in all patients fulfilling the inclusion and exclusion criteria. Data with regards to age, sex, diabetes, dyslipidemia were collected and analysed by appropriate statistical methods. Results: A total of 50 patients with 30 males and 20 females presented with anginal chest pain, of the total 50 patients, 19 were smokers, 9 had family history of coronary artery disease, 31 patients had hypertension, 14 had diabetes and 39 of the study population had dyslipidemia. Coronary angiography showed 48% of the study population had a single vessel disease and 32% with double vessel disease. Left anterior descending artery (LAD) was predominantly involved with 25 (50%) of total cases. Single vessel disease was common among those with hypertension and dyslipidemia. Conclusions: Coronary artery disease (CAD) is common in young adults. Dyslipidemia, hypertension and smoking are the most important risk factors associated with CAD. Left anterior descending artery is commonly involved in CAD followed by right coronary artery.